Q&A: Professor Robert Sutton on communicating difficult decisions as a leader - McGinn, Daniel (Harvard Business Review)
One of the responsibilities of leaders is to deliver bad news: that the company is pulling the plug on a beloved project, forgoing raises or bonuses, implementing return-to-office mandates$1 (Bor even eliminating jobs. When the economy weakens, more companies make these choices, requiring leaders to communicate them in a way that minimizes the damage to morale.- Reproduced s